Structure and formation features of quaternary deposits of the West Polesie because of its amber content - Bahdasarau, Maksim A.; Kukharyk, Yauhen A. (Journal of the Belarusian State University. Geography and Geology, 2017)
This work is concerned with study of structure and formation features of quaternary deposits of the West Polesie because of its amber content. There were found out the stratigraphic features of occurrence and paleogeographic conditions of aggregation of amber geological positions within the limits of Belarusian and Ukraine parts of the West Polesie’s territory. The lithological composition of amber detritus concentration in deposits of various genetic types, the source of mineral income into sedimentary series that contain it in redeposit condition were analyzed. On the basis of the consolidation of factual material, there was shown the difference of amber aggregation process in glacial and interglacial periods. The main criteria of finding prospective amber territories were defined.